ChemInform Abstract: Synthesis and Reactivity of N‐Alkyl Carbamoylimidazoles: Development of N‐Methyl Carbamoylimidazole as a Methyl Isocyanate Equivalent. Issue 16 (28th March 2013) - Duspara, Petar A.; Islam, Md. Sadequl; Lough, Alan J.; Batey, Robert A.
Abstract The applied imidazole reagent can be easily prepared from methylamine hydrochloride.